Implementasi Kebijakan Pelayanan Publik Bagi Masyarakat Penyandang Cacat - Ika Devy Pramudiana (DIMENSI - Jurnal Sosiologi, 2016)
This research aims to analyze public policy and service implemented to people with disability. This research is important and interesting because of lack of government’s attention in fulfilling the rights of people with disability. Public services in Indonesia have not been responsive to the community with special needs, including vulnerable groups, people with disabilities, lack of attention to people with disabilities appear to have a lot of teredianya services, public access or public facilities. Understanding of all functions of government law No. 4, 1997 (UU No. 4 Tahun 1997) on access for disabled people and government regulation No. 43/1998 (PP. No. 43/1998) concerning the development of social prosperity for the disabled is still low. Provision of services accessible to all citizens (inclusive) in the public service sector is still not a top priority of government. This study was a qualitative research, where researchers aimed to describe and analyze the implementation of public services provided in relation to the disabled. Here the important role of government in memperhatiakan people with disabilities, much needed public service should have been held by thegovernment is able to meet the needs of all citizens and can be accessed by all citizens without exception.